The poor agricultural system in Africa, who is to blame? - Nchanji, Eileen Bogweh; Nchanji, Yvonne Kiki; Adolwa, Ivan S. (Scientific Research Publishing, Inc., 2021)
Although agriculture is the backbone of the African economy, it has faced considerable challenges in the past sixty years. Africa has moved from being a self-sufficiency continent before the 1960s, to net food importers, with a handful of countries facing severe food shortages from drought, desertification, climate change and wars. In this article, we use the case of Northern Ghana to explore some of the salient dynamics that have resulted in the current crisis in the African agricultural sector over time. Using historical and contemporary evidence gathered from Northern Ghana during several field trips from 2013 to 2015, we argue that practices adopted as a result of colonial influence in combination with socio-economic and biophysical factors and ineffective economic policies have contributed immensely to the poor state of agriculture in Africa. Note should be taken that most of these economic policies have origins from the Structural Adjustment Policies and the Poverty Reduction Strategy Papers. We conclude that our agricultural systems can be improved if policies are inclusive, equitable and sustainable and also if there are synergies between international or government organisations implementing agricultural projects over time and space.